The effectiveness of teaching science subjects through English medium: A narrative analysis of teacher experiences and perceptions in Sri Lankan secondary schools - Wedikkarage, Lakshman (International review of education, 2018)
This article analyses four narratives told by four teachers teaching science subjects in four different public secondary schools in the district of Gampaha in Sri Lanka. Gampaha is the second most populous district in Sri Lanka, and is known for excellent results in General Certificate of Education (Advanced Level) exams which school leavers sit at the end of the secondary school cycle. The teachers' narratives focus on the policy and practice of teaching science subjects through English at secondary level, which was reintroduced in a small number of selected government schools in Sri Lanka in 2002. After using the two local languages, Sinhala and Tamil, for nearly half a century, the Sri Lankan education authorities decided to bring back the English medium to the teaching of science subjects at secondary level as a third language option. One of the policymakers' reasons was an apparent decline in the English-language fluency of students at this level. To implement the new policy, science teachers (who had themselves been taught in Sinhala or Tamil) were asked to teach in English. More than a decade into the English-medium option, the author interviewed four of them. Their testimonies about their experiences in teaching science subjects offer valuable insights into the difficulties experienced by both teachers and students when teaching and learning in a foreign language such as English. The author's analysis of his respondents' statements reveals hidden realities which challenge the benefits of reintroducing English as a medium of instruction (MOI) for science subjects. Thus, the lived experiences of the teachers may help to inform language policy in education in Sri Lanka, and perhaps also in other countries. Efficacité de l'enseignement des sciences en anglais: analyse narrative des expéri ences et perceptions d'enseignants secondaires au Sri Lanka - Cet article présente quatre récits d'enseignants en sciences exerçant dans différentes écoles publiques secondaires du district srilankais de Gampaha. Il s'agit du deuxième district le plus peuplé du pays, connu pour ses excellents résultats aux examens du certificat général d'éducation (niveau avancé) que passent les élèves sortants à la fin du cycle secondaire. Les récits des enseignants portent sur la stratégie et la pratique de l'enseignement au niveau secondaire de matières scientifiques par le biais de l'anglais, réintroduit en 2002 au Sri Lanka dans un petit nombre d'écoles publiques sélectionnées. Après avoir utilisé les deux langues locales, le cingalais et le tamoul, pendant presque un siècle, les autorités éducatives srilankaises ont décidé de réintroduire l'anglais à titre de troisième langue en option pour enseigner des matières scientifiques au niveau sec ondaire. L'un des arguments des décideurs était un déclin apparent dans la maîtrise de l'anglais parmi les lycéens. Afin d'appliquer la nouvelle stratégie, les professeurs de sciences (qui ont eux-mêmes reçu un enseignement en cingalais ou en tamoul) ont été priés d'enseigner en anglais. Plus de dix ans après l'introduction de l'anglais en op tion, l'auteur a interviewé quatre enseignants concernés. Leurs témoignages sur leurs expériences de l'enseignement de matières scientifiques fournissent de précieuses in formations sur les difficultés rencontrées à la fois par les enseignants et par les élèves, pour enseigner et apprendre dans une langue étrangère telle que l'anglais. L'analyse effectuée par l'auteur des déclarations de ses répondants révèle des réalités occultées, qui mettent en question les bienfaits de la réintroduction de l'anglais comme langue d'instruction dans les matières scientifiques. Les expériences de ces enseignants pourraient ainsi contribuer à alimenter la politique linguistique du système éducatif srilankais, éventuellement aussi dans d'autres pays.